Abandonment of health monitoring of babies of mothers with vertical transmission grievance - Bianca Machado Cruz Shibukawa; Maria de Fátima Garcia Lopes Merino; Vanessa Paula Lanjoni; Franciele Aline Machado de Brito; Marcela Demitto Furtado; Ieda Harumi Higarashi (Universidade Federal do Ceará, 2021)
Objective: to analyze the abandonment of the health monitoring of babies of mothers with vertical transmission grievance. Methods: a retrospective documental study. The data came from children's records stratified as high risk by the Paranaense Mother Network Program, due to being daughters of women diagnosed with syphilis, toxoplasmosis or Human Immunodeficiency Virus in the gestational period, attended in a reference center of maternal-infant care. For the analysis of factors associated with abandonment of treatment, univariate analysis and Fisher's Exact Test with sociodemographic variables were performed. All ethical precepts were observed. Results: a total of 136 medical records were analyzed. The cases with the highest abandonment rate were the children of women with toxoplasmosis and gestational syphilis, presenting rates of 48.4% and 45.7%, respectively. Conclusion: the abandonment of baby health monitoring is recurrent. The reasons for frequent abandonment were: lack of active search, lack of transportation and unforeseen family events.